Educational guidance strategies in the case of undergraduate pupils of student mobility - Izurieta, María Rosario (2018)
This work attends to identify and characterize the educational guidance strategies in the case of undergraduate pupils of student mobility. Although there are wide national and international backgrounds related to guidance, investigations on educational guidance in the case here considered are considerably few. In our context we can take into account a growing increase of students who decide to study undergraduate degree at national universities, which leads to the need to develop guidance intervention strategies that accompany and promote their educational histories. In this work at first place we describe the backgrounds and characteristics of the student mobility at the Psychology School of the National University of La Plata (2007-2017), from the systematization and analysis of institutional documentary sources. Secondly, the educational guidance actions implemented with students who studied subjects in the second semester of the 2017 school year are specifically analyzed. For this purpose, a semi-structured interview was designed and implemented, organized in different axes, which was applied to the aforementioned students. Finally, results are discussed and intervention strategies are proposed that consider institutions and significant actors for student mobility processes at the university level.